Lead Accumulation of Siam Weed (Chromolaena odorata) Grown in Hydroponics Under Drought-stressed Conditions: 10.32526/ennrj/20/202100178 - Srirueang, Chanaradee; Gongseng, Nuttamon; Saeng-ngam, Sukhumaporn; Jampasri, Kongkeat (Environment and Natural Resources Journal, 2021)
The phytoremediation potential of Siam weed (Chromolaena odorata) was tested in lead (Pb) contaminated nutrient media with 5% (w/v) of polyethylene glycol (PEG) 6000 induced drought stress conditions. The plant was treated with 0, 5, 10, 20, and 50 mg/L Pb for 15 days. Different concentrations of Pb or in combination with PEG had no effect on plant growth parameters. Drought reduced water content (WC) (p<0.05), but did not affect the reduction of chlorophyll content and photochemical efficiency in plant tissues after 15 days of treatment. Under drought conditions, plants showed the largest Pb accumulation in roots (5,503.7 mg/kg) and exhibited the highest uptake at 50 mg/L solution (18.24 g/plant), but the translocation factor values (TFs) of Pb from root to shoot were all less than 1. Under both drought and non-drought conditions, the bioconcentration factor values (BCFs) decreased with increasing Pb concentrations. According to BCFs and TFs, C. odorata may be promising for phytostabilization of Pb. Based on high biomass, tolerance, and Pb uptake, the result of this hydroponic study test reveals that C. odorata has a good potential for developing Pb phytoremediation strategies in drought-stressed conditions.